PERENCANAAN JARINGAN KOMUNIKASI BERBASIS VOIP MENGGUNAKAN CISCO UNIFIED COMMUNICATION MANAGER - Eka Satryawati; Muhamad Lutfi; Ade Surya Budiman (Institut Teknologi dan Bisnis Swadharma, 2021)
Computer network technology is growing rapidly. Computer communication technology is very fast developing and has developed application systems such as VoIP (Voice Over Internet Protocol). This technology works by converting sound into a digital format that is sent over the internet. Prior to the current implementation, the voice or telephone communication network used at the head office of PT. SequisLife uses a PSTN-based telephone. This, of course, wastes the company's operational financing. By using VoIP (Voice Over Internet Protocol) to create a very appropriate solution to resolve what happened to the company. Building a VoIP server requires an open source based application, namely the CUCM application, with sufficient CUCM applications requiring functions and benefits that are stable and safe to use. To build a VoIP-based communication network only requires a separate server, ip phone, router and internet network connection. With the results obtained by communication planning with VoIP-based technology, employees or users associated with the environment of this company in one another cooperation safely and smoothly and low cost